The Correspondence Between Executive Functioning and Academic Achievement Among Children with Prenatal Alcohol Exposure - Kristene Cheung; Susan Doyle; Kylee Clayton; Ana Hanlon-Dearman; Jo Ann Unger; Caelan Budhoo; Alyssa Romaniuk (Children)
Background/Objectives: Canadian guidelines for diagnosing fetal alcohol spectrum disorder (FASD) strongly recommend using direct measures to assess brain domains whenever possible. Executive functioning, one of the brain domains assessed, can be measured using direct and indirect measures; however, research has found discrepancies between these two forms of assessment and has not examined this relationship using ratings from the newest version of one of the most commonly used indirect measure of executive functioning, the second version of the Behavior Rating Inventory of Executive Functioning (BRIEF2). Academic achievement may also help explain discrepancies between these forms of assessment, especially in indirect executive functioning skills at school, because many of the items on the BRIEF2 Teacher Form are related to school skills. This study aimed to examine the relationship between direct measures of executive functioning, indirect measures of executive functioning, and academic achievement. Methods: Charts of 74 children who completed an FASD diagnostic assessment in Canada were included in this study (61% males; 58% with FASD; Mage = 11.77). Direct and indirect measures of executive functioning across settings and academic achievement were assessed. Results: Few correlations between corresponding BRIEF2 and direct measures of executive functioning were significantly associated. There were several significant correlations between academic achievement and (a) educator ratings on the BRIEF2 and (b) direct measures of executive functioning. None of the caregiver ratings on the BRIEF2 were significantly associated with academic achievement. Conclusions: The results suggest that academic performance is related to BRIEF2 ratings of executive functioning skills at school and direct measures of executive functioning. Aside from a few exceptions, direct and indirect measures of the same executive functioning skill were not correlated.